COMPARISON OF JAVASCRIPT FRAMEWORKS REACT, ANGULAR AND VUE.JS IN THE STUDY OF PERFORMANCE AND SCALABILITY OF WEB APPLICATIONS - NEDILKO, OLHA; SACHUK, VICTORIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article focuses on the comparative study of three of the most widely used JavaScript frameworks—React, Angular, and Vue.js—in the context of web application performance and scalability. In recent years, JavaScript frameworks have become the foundation of modern web development, providing developers with efficient tools for building dynamic and interactive user interfaces. Each framework offers its own architectural approach, ecosystem, and performance characteristics, which significantly influence the overall efficiency and maintainability of a web project. React, developed by Facebook, is a library oriented toward creating reusable UI components. Its virtual DOM implementation ensures high rendering performance, while its unidirectional data flow simplifies debugging and enhances predictability. However, scaling large applications often requires integrating additional libraries for routing, state management, and data handling. Angular, supported by Google, represents a full-featured framework with a well-defined structure, two-way data binding, and dependency injection mechanisms. These features make Angular suitable for enterprise-level solutions and large teams, though its steep learning curve and complex syntax can present challenges for newcomers. Vue.js, in turn, combines the advantages of React’s component-based design and Angular’s declarative templates, offering an easy learning path and high adaptability. Its lightweight core and excellent documentation make Vue a popular choice for small to medium projects or rapid prototyping. The analysis concludes that the selection of a JavaScript framework should be based on the project’s complexity, team expertise, and scalability goals. React is best suited for flexible, performance-oriented solutions; Angular excels in large structured applications; and Vue.js offers an optimal balance between simplicity and functionality. Understanding these distinctions allows developers to optimize web application development and ensure efficient long-term maintenance.